A stochastic resonance etection algorithm based on orthonormalized basis function for magnetic anomaly detection - Dai, Fan; Peng, Dongliang; Chen, Zhikun; Li, Tao; Weng, Yiming; Zhuo, Renxiong; Liu, Baoyang (Review of scientific instruments, 2023)
To address the problem that the performance of the detector in airborne magnetic anomaly detection (MAD) is terrible, a stochastic resonance (SR) detection algorithm based on orthonormalized basis function (OBF-SR) is proposed for MAD under low signal-to-noise ratio conditions. The signal contaminated by noise is first preprocessed by the OBF method, where the sum of the three components in the OBF space is selected as the SR system input. Then, a parallel SR system with different initial states is designed to detect the signal. Finally, the simulation analysis of MAD methods is performed to draw a comparison between the OBF-SR method, the typical SR method, and the OBF method. The results show that the OBF-SR method outperforms the SR and OBF methods in the detection probability and detection range under the same conditions.